Downscaling climate projections for the Peruvian coastal Chancay-Huaral Basin to support river discharge modeling with WEAP - Olsson, T. (2017)
Study region The Chancay-Huaral (CH) coastal river basin in the Lima Region, Peru, between the Pacific Ocean and the Andean Cordillera. Study focus Climate change impacts on annual and monthly discharges in the CH Basin are assessed for the future period 2051–2080. Hydrological modeling is sensitive to biases in input variables. Therefore, bias-corrected time series of temperature and precipitation from 31 General Circulation Models (GCMs) with the emission scenarios RCP4.5 and RCP8.5 (Representative Concentration Pathways) were used as inputs for the Water Evaluation and Planning System model (WEAP). Bias correction and downscaling of the GCMs were implemented using a quantile mapping method. New hydrological insights for the region On average, GCMs indicate increased annual mean temperatures by 3.1 °C (RCP4.5) and by 4.3 °C (RCP8.5) and precipitation sum by 20% (RCP4.5) and by 28% (RCP8.5). With increasing total precipitation, river discharges are also found to increase, but the variability among the GCMs is considerable. The largest increases in monthly discharge are projected to occur in the wet season (November − April) − with up to 31% increase of December multi-model mean. Despite the larger annual discharge for the mean multi-model result, discharges in the dry season may decrease according to some GCMs, showing the need for an adapted future water management.